Protein aggregation, metals and oxidative stress in neurodegenerative diseases. (26th October 2005) - Tabner, B.J.; El-Agnaf, O.M.A.; German, M.J.; Fullwood, N.J.; Allsop, D.
Abstract : There is clear evidence implicating oxidative stress in the pathology of many different neurodegenerative diseases. ROS (reactive oxygen species) are the primary mediators of oxidative stress and many of the aggregating proteins and peptides associated with neurodegenerative disease can generate hydrogen peroxide, a key ROS, apparently through interactions with redox-active metal ions. Our recent results suggest that ROS are generated during the very early stages of protein aggregation, when protofibrils or soluble oligomers are present, but in the absence of mature amyloid fibrils. The generation of ROS during early-stage protein aggregation may be a common, fundamental molecular mechanism underlying the pathogenesis of oxidative damage, neurodegeneration and cell death in several different neurodegenerative diseases. Drugs that specifically target this process could be useful in the future therapy of these diseases.